Hunter-gatherers across the great Adriatic-Po region during the Last Glacial Maximum: Environmental and cultural dynamics. (20th April 2021) - Peresani, Marco; Monegato, Giovanni; Ravazzi, Cesare; Bertola, Stefano; Margaritora, Davide; Breda, Marzia; Fontana, Alessandro; Fontana, Federica; Janković, Ivor; Karavanić, Ivor; Komšo, Darko; Mozzi, Paolo; et al.
Abstract: During the Last Glacial Maximum (LGM, 30 to 16.5 ka ago), the Great Adriatic-Po Region (GAPR) was deeply affected by the spread of glaciers from the Alps to the southern foreland and by the dropping of the sea level to -120 m amsl. The combination of these two events triggered the aggradation of the Great Po Plain (GPP), a vast flat area between the Alpine chain, the Italian Peninsula and the north-western Balkan Peninsula, physically and ecologically featured through a range of palaeogeographic and palaeoecological conditions. The low-elevated Prealpine sectors and the Alpine foothills supported more extensive forest stands, due to increased orographic rainfall. These were open boreal forests which persisted throughout the LGM, while open woodlands, steppes, semideserts and wetlands occupied the lowlands. A complex ecogradient, including both an Alpine and a continental timberline, is documented by the fossil records at the NE Alpine border, with a larch-pine forest-steppe belt, in contact with steppes and loess areas extending in the plain, on the dry extreme of the gradient. Still, edaphic wetlands occupied the waterlogged silty soils in the lowlands. Other areas, marked by active geodynamic processes, supported semideserts, i.e. grooves of xerophytic herbs and shrubs. Enhanced aridity and the development of deflation areas, prompted the accretion of loess cover at the northern and southern margins of the GPP. Fauna recorded the gradual disappearance of mammoth, woolly rhino and giant deer, together with cave bear. Gravettian and Epigravettian hunter-gatherer groups inhabited the GPP, although their presence and settlement dynamics at the margins and across this region has long been questioned. As a matter of fact, a handful of archaeological sites composes a patchy record of the peopling of the plain itself. At the northern rim of the GAPR, characterized by a well-developed karst region, several caves and rock shelters record the presence of hunters of bisons and horses at the margins of the GPP and ibexes and cave bears in some hilly landscapes. Nonetheless, evidence of contacts across this area is provided by the exploitation of chert sources and by stylistic and technical similarities in the lithic industries. The work resumes the currently available multidisciplinary data and adds new petroarchaeological evidence for reconstructing the settlement dynamics of the Gravettian - Epigravettian hunter-gatherers in this vast region up to the early Late Glacial, when the Prealpine and the Apennine foothills, along with the Dinarids, were persistently settled.